Radiation isocenter measurement devices and methods and 3-D radiation isocenter visualization systems and related methods - Jenkins, Todd; Allison, Ron R.; Sibata, Claudio (My University, 2008)
A three-dimensional phantom assembly for use with a radiation treatment device includes a three-dimensional support member having at least two, spaced apart opposed surfaces configured to hold at least one generally planar radiation sensitive dosimeter sheet such that the dosimeter sheet generally conforms to a shape defined by the two opposed surfaces. During irradiation, a radiation beam trajectory passes through the two opposed surfaces. Related systems methods for determining a radiation isocenter and/or generating a 3-D visualization of the radiation isocenter using radiation patterns obtained using a phantom are also described.